A method for producing a low-hydroxyl synthetic quartz glass preform
Patent Information
- Application Number
- CN202611215902.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0008]针对现有技术的缺陷,本申请的目的在于提供一种低羟基合成石英玻璃母材的制备方法,以解决现有技术中存在的传统低温脱氯工艺气体扩散不均、径向氯梯度累积严重导致光学非均匀性指标偏高、高温变温工艺因粉体密度分层引发氯浓度断崖式突变固化为永久性折射率台阶起伏、工艺参数固化仅能适配单一固定尺寸坯体无法兼容D200~600mm超大跨度尺寸粉棒生产的技术问题
(1)本申请采用六段式一体化复合工艺,包括粉体预收缩均质阶段、低温梯度预制阶段、中温梯度均衡校准阶段、中高温梯度收敛抵消阶段、后处理阶段以及最后的高温透明烧结阶段,通过热收缩均质配合后续氯梯度预制、均衡和抵消的多步骤设置,解决现有技术氯梯度带来的光学缺陷,实现低羟基、高光均、高致密透明化的高端合成石英玻璃母材的制备。
Smart Images

Figure CN122725611B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of high-purity quartz glass preparation technology, and more specifically, relates to a method for preparing a low-hydroxyl synthetic quartz glass masterbatch. Background Technology
[0002] The core process for preparing low-hydroxyl, high-purity, and low-defect quartz glass matrix is the chlorination and oxidative dechlorination treatment of porous quartz powder (or porous quartz powder rods, porous quartz bulk, or porous quartz preform). In the industry, the process typically involves first mixing oxyhydrogen flame and silicon tetrachloride vapor to prepare a porous silica body with a certain density. Then, the powder is placed in a reaction vessel, and a dehydrating agent (usually chlorine) is introduced. The hydroxyl groups inside the powder are removed by the reaction of chlorine and water molecules. Residual chlorine impurities are then removed by oxygen. Finally, the treated powder is heated to the glass transition temperature (usually above 1450℃) in the reaction vessel to obtain a transparent matrix that meets certain optical uniformity requirements and achieves the target of having less than 1 ppm of hydroxyl groups.
[0003] Existing conventional dechlorination processes take into account that loose powders will shrink at high temperatures. For example, in the range of 1100-1300℃, powders are prone to shrinkage cavities, densification, and skeletal collapse. Therefore, the mainstream processes in the industry all use a temperature range below which the powder begins to shrink cavities for dehydroxylation and dechlorination treatment. They are generally concentrated in the low temperature constant temperature range of 800℃ to 1000℃ to complete the chlorination and oxidative dechlorination reactions. This avoids structural defects such as premature sintering shrinkage, deformation, and cavitation collapse of the powder, and ensures the integrity of the green body structure.
[0004] However, this type of low-temperature dechlorination process has significant inherent technical defects: the chlorine desorption reaction rate is slow and the dechlorination motive force is weak under low-temperature conditions, the dechlorination process has a long time span, there are radial diffusion differences in the internal pore structure of the powder, chlorine and oxygen penetrate and are removed layer by layer from the outside to the inside, which easily forms a continuous and accumulated chlorine concentration gradient in the cross section of the green body, ultimately resulting in a high optical uniformity value of the finished quartz glass and poor overall optical uniformity.
[0005] To improve optical uniformity, existing technologies generally employ a high-temperature variable-temperature process. This involves raising the temperature from a low temperature to 1100℃-1300℃ to enhance dechlorination efficiency, shorten dechlorination time, and suppress gradient accumulation, effectively reducing the optical uniformity of the finished product. However, this high-temperature variable-temperature process also introduces more serious optical structural defects: during the deposition and forming process, porous quartz powder is affected by fluctuations in airflow, temperature, and deposition rate, resulting in natural axial and radial density stratification in the green body. This forms a microstructure with alternating high and low porosity, which is an inherent property of the powder and cannot be completely eliminated through the initial forming process.
[0006] During conventional high-temperature heating, the low-density regions of the powder exhibit porous structures, excellent gas thermal conductivity, and high localized actual temperatures, while the high-density regions have dense pores, high thermal resistance, and low localized actual temperatures. A significant localized temperature difference forms at the density separation interface, causing the two sides of the separation to operate under two different dominant mechanisms of the silicon-chlorine reaction. In the relatively low-temperature high-density region, the silicon-chlorine solid solution reaction dominates, with a large number of chlorine impurities locked in the crystal lattice and difficult to remove. In the relatively high-temperature low-density region, thermal desorption is dominant, with chlorine impurities rapidly removed and escaped. Ultimately, a sharp drop in chlorine concentration occurs at the density separation interface, solidifying into a permanent refractive index step and localized optical distortion.
[0007] In summary, traditional processes suffer from irreconcilable core contradictions, resulting in poor optical uniformity and large refractive index variations in the produced synthetic quartz glass preforms. Furthermore, they are only suitable for single-size preforms and cannot be compatible with the production of powder rods of different diameters. Currently, the industry lacks a process that can differentiate and control powder rods with ultra-large diameters ranging from D200 to 600mm, making it impossible to simultaneously achieve the high-end manufacturing requirements of quartz glass, such as high gloss uniformity, absence of abrupt steps, complete preform structure, and mass production adaptability to multiple sizes. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the purpose of this application is to provide a method for preparing low-hydroxyl synthetic quartz glass masterbatch, thereby solving the technical problems existing in the prior art, such as uneven gas diffusion in traditional low-temperature dechlorination processes, severe accumulation of radial chlorine gradients leading to high optical non-uniformity indices, precipitous chlorine concentration abrupt changes due to powder density stratification in high-temperature variable-temperature processes resulting in permanent refractive index step fluctuations, and process parameters that can only be adapted to single fixed-size blanks and cannot be compatible with the production of ultra-large span powder rods of D200~600mm.
[0009] To achieve the above objectives, in a first aspect, this application provides a method for preparing a low-hydroxyl synthetic quartz glass masterbatch, comprising the following steps: S1. The porous quartz powder rod is heat-treated in an inert atmosphere at 1250~1350℃ for several hours to cause the porous quartz powder rod to shrink, reduce the overall density difference, and obtain the pre-shrinked porous quartz powder rod. S2. At a temperature of 700~900℃, a He / Cl2 mixed gas is introduced to perform dehydroxylation treatment on the pre-shrinked porous quartz powder rod, while simultaneously constructing a reverse chlorine gradient with a high outer and low inner temperature within the porous quartz powder rod. S3. Heat to 850~950℃, introduce He / O2 mixed gas for low-temperature dechlorination, and at the same time homogenize the reverse chlorine gradient formed in step S2 to reduce the chlorine concentration gradient; the processing temperature of step S3 is 50~150℃ higher than that of step S2 but does not exceed 950℃. S4. At a temperature of 1000~1100℃, a He / O2 mixed gas is introduced to carry out medium-high temperature dechlorination. During the high-temperature chemical reaction dechlorination process, the high density in the middle region and the low density in the edge region of the powder rod are utilized. The Cl contained in the middle region is difficult to diffuse out, while the Cl in the edge region is relatively easy to remove, forming a chlorine gradient with a low outer and high inner density. This cancels out the reverse chlorine gradient with a high outer and low inner density formed in step S2. S5. After the high-temperature dechlorination in step S4 is completed, the temperature is raised to 50-200℃, and inert gas is introduced to purge the furnace body to remove free chlorine molecules in the powder rod; then the temperature is lowered to room temperature to obtain the powder rod that has completed dehydroxylation and dechlorination. S6. The powder rod obtained in step S5 is heated to 1450~1550℃ and subjected to constant temperature transparent sintering under an inert gas protective atmosphere to complete the densification and glassy transparent transformation of the powder rod, eliminate powder pores and micro-loose structure, and obtain low hydroxyl synthetic quartz glass matrix.
[0010] Preferably, the porous quartz powder rod has a diameter of D200~D600mm and a bulk density of 0.25~0.5g / cm³.
[0011] Preferably, the heating rate in step S1 is controlled at 4~7℃ / min, and the heating treatment time is 2-4h.
[0012] Preferably, in step S2, a He / Cl2 mixed gas with a flow rate of 20~30 slm is introduced to construct a reverse chlorine gradient with a higher outer layer and a lower inner layer in the porous quartz powder rod. The process time t1 is calculated based on the Fick one-dimensional unidirectional gas penetration diffusion model according to the differences in powder rod diameter. ; ; In the formula: The duration of the gradient prefabrication process; The radial diffusion penetration depth of the powder rod; The effective diffusion coefficient of Cl2 in the low temperature range of 700~900℃; =20-40min; The gas-phase diffusion constant of Cl2; The porosity of the powder; The degree of tortuosity of the passageway.
[0013] Preferably, in step S3, a He / O2 mixed gas with a total flow rate of 10~30 slm is introduced, and the process duration t2 is calculated based on the difference in powder rod diameter according to the bidirectional diffusion equilibrium mechanism. ; In the formula: The diffusion coefficient of He / O2 mixed gas within the medium-temperature calibration range of 850~950℃.
[0014] Preferably, in step S4, a He / O2 mixed gas with a flow rate of 20~30 slm is introduced, and the temperature is increased to 1000~1100℃ at a heating rate of 1~8℃ / min to carry out a high-temperature chemical reaction.
[0015] Preferably, the process time t3 of step S4 is calculated based on a high-temperature solid solution reaction kinetic model: ; In the formula: This represents the average chlorine content in the powder bar; For gradient cancellation balancing efficiency; The reaction rate constant is at 1050℃; This is the partial pressure of oxygen. This represents the effective reaction surface area of the powder.
[0016] Preferably, in step S4, the temperature is increased to the critical range of solid solution reaction of 950-1000℃ at a heating rate of 1-2℃ / min, and in other heating ranges, the heating rate is increased to 3-7℃ / min.
[0017] Preferably, in step S5, pure He gas with a flow rate of 20-30 slm is introduced to purge for 150-250 min; then the temperature is reduced to room temperature at a rate of 1-5 °C / min.
[0018] Preferably, in step S6, 20-30 slm of pure He gas is introduced and sintered at a constant temperature for 120-180 min.
[0019] Overall, the technical solutions conceived in this application have the following beneficial effects compared with the prior art: (1) This application adopts a six-stage integrated composite process, including a powder pre-shrinking homogenization stage, a low-temperature gradient pre-fabrication stage, a medium-temperature gradient equalization calibration stage, a medium-high temperature gradient convergence and cancellation stage, a post-processing stage, and a final high-temperature transparent sintering stage. By combining thermal shrinkage homogenization with subsequent chlorine gradient pre-fabrication, equalization, and cancellation in a multi-step setting, the optical defects caused by the chlorine gradient in the prior art are solved, and the preparation of high-end synthetic quartz glass master material with low hydroxyl content, high light uniformity, and high density and transparency is realized.
[0020] (2) The preparation method of the synthetic quartz glass master material of this application is specifically adapted to the mass production of ultra-large span quartz powder rods with D200~D600mm and bulk density of 0.25~0.5g / cm³. It has the ability to adjust the time for different sizes and densities. It can match the corresponding diffusion and reaction time according to different powder rod diameters and different bulk densities, solving the industry pain point that traditional processes can only adapt to a single specification, and the performance will fail when the size and density change. Without reducing production efficiency and ensuring the integrity of the green body structure, it can achieve a high-end general preparation effect of high gloss uniformity, no optical defects, and high density and transparency of green bodies of all specifications.
[0021] (3) The method of this application has a diameter-linked duration control mechanism. For powder rods with different diameters ranging from D200 to 600 mm, the corresponding penetration reference duration and enrichment delay are matched, so that the reverse chlorine gradient with the outside high and the inside low can be prefabricated in the entire range of billets at 700~900℃, while the hydroxyl content of the whole cross section is controlled below 0.5ppm, and there are no refractive index defects in low-temperature forming, realizing the synchronous and controllable prefabrication of ultra-large span multi-size billets; combined with the progressive temperature control process of the exclusive temperature zone of gradient calibration at 850~950℃, the temperature rise is 50~150℃ compared with the low-temperature prefabrication temperature zone, and the temperature is strictly controlled not to exceed 950℃, forming a gradient progressive and step-by-step temperature control logic; combined with the gradient substrate of ultra-large span multi-size differentiated duration prefabrication and the fixed oxygen partial pressure closed-loop stabilization control, it can The original reverse gradient of the D200~600mm full-size billet is uniformly and finely adjusted to a lower level to adapt to the high-temperature solid solution gradient of billets of different sizes, ensuring a flat and distortion-free refractive index profile for billets of all diameters with ultra-large spans throughout the process. Then, a segmented differentiated heating mechanism is adopted to adapt to the reaction characteristics of multi-size billets with ultra-large spans of D200~600mm. Rapid heating in the conventional range ensures efficiency, while slow heating in the 950~1000℃ solid solution critical range avoids abrupt changes in the solid solution ratio. In the 1050℃ high-temperature mass production temperature range, the bidirectional gradient of the full-size billet is fully offset, significantly reducing the radial change amplitude of the solid solution ratio. This fundamentally improves the discontinuous steps of refractive index and optical distortion in the mass production of ultra-large span full-size billets, balancing mass production efficiency and universal adaptability for all sizes.
[0022] (4) The optical properties and purity of the synthetic quartz glass matrix prepared in this application are significantly improved, solving the problems of chlorine residue gradient accumulation, poor light uniformity, and abrupt pattern changes in traditional low-temperature processes. This application effectively improves the drawbacks of uneven gas diffusion inside the powder and effectively improves the defects of radial chlorine gradient accumulation. The optical non-uniformity index of the D300mm glass matrix is stably controlled below 2ppm, which is a significant improvement compared to the light uniformity level of 7~10ppm in traditional low-temperature processes. At the same time, the hydroxyl content of the whole aperture is stably less than 0.5ppm, the purity of the finished product is significantly improved, and it fully meets the application standards of high-end optical devices.
[0023] (5) The preparation method of the synthetic quartz glass matrix in this application eliminates the defect of abrupt change in refractive index and improves the inherent optical distortion problem of high-temperature process. Through the reverse gradient pre-compensation and high-temperature gradient convergence cancellation mechanism, the problem of abrupt change in chlorine concentration caused by powder density stratification and interface temperature difference is effectively solved, and the step depth of >2ppm in the traditional high-temperature process is reduced to below 0.5ppm, so that the refractive index profile has no discontinuous and abrupt fluctuations, and remains continuous and flat throughout the process, thus improving local permanent optical distortion.
[0024] (6) This application realizes the adaptive production of powder bars with ultra-large span size of D200~600mm, which solves the shortcomings of traditional processes that can only adapt to a single specification and whose performance fails when the size changes. It effectively broadens the process tolerance window and adaptation range, greatly improves the performance fluctuation problem between batches, significantly improves the stability of mass production, and realizes the technical unity of complete structure, high gloss uniformity, no step distortion, ultra-large span multi-size adaptation, and efficient mass production.
[0025] (7) This application can stably achieve finished product light content of 1.62ppm, hydroxyl content <0.5ppm, step depth <0.5ppm and no step number, high density, full transparency without pores, complete structure without defects, strong batch stability, and can be adapted to industrial high-efficiency mass production. Attached Figure Description
[0026] Figure 1 This is a flowchart of the preparation method of the low-hydroxyl synthetic quartz glass masterbatch of this application; Figure 2 This is a test diagram of the optical non-uniformity of a D300mm disc of glass substrate in Embodiment 1 of this application; Figure 3 This is a wavefront distortion curve of a D300mm circular glass substrate from Embodiment 1 of this application; Figure 4 This is a test diagram of optical non-uniformity of a D300mm disc of glass substrate, which is Comparative Example 2 of this application. Figure 5 This is a wavefront distortion curve of a D300mm circular glass substrate, which is Comparative Example 2 of this application. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0028] This application addresses the multiple technical shortcomings of existing quartz glass dechlorination processes, aiming to solve the following three core technical problems: First, it solves the problems of uneven gas diffusion and severe radial chlorine gradient accumulation in traditional low-temperature dechlorination processes, thoroughly optimizing the optical uniformity of the finished product. It can improve the optical uniformity index of D300mm diameter quartz glass parent material from 5ppm~10ppm in traditional low-temperature processes to below 2ppm, and the hydroxyl content of the entire aperture is less than 0.5ppm, meeting the standards for high-end optical applications. Second, it solves the core problem of discontinuous and abrupt step fluctuations in refractive index profile caused by powder density stratification and interface temperature difference in existing high-temperature variable temperature processes, eliminates the cliff-like abrupt change in chlorine concentration, reduces the step depth from >2ppm to below 0.5ppm, eliminates the number of steps, completely eradicates local optical distortion, and achieves a continuous and smooth refractive index profile. Third, it breaks through the limitations of traditional single-size adaptation and, through the diameter-time coupling control mechanism, is compatible with the mass production of powder bars in the ultra-large range of D200~600mm, which broadens the process tolerance window and adaptation range, greatly improves the stability of batch production, and achieves structural integrity, high gloss uniformity, no step distortion, and multi-size adaptation.
[0029] The formation mechanism of defects in traditional processes: The natural density stratification structure (high in the middle and low at the edges) formed during powder forming causes local temperature differences at the stratification interface under high-temperature processing. The regions on both sides of the interface trigger competitive reactions of Si-Cl solid solution locking and thermal desorption, ultimately forming a cliff-like abrupt change in chlorine concentration inside the green body, which solidifies into an irreversible step change in refractive index. In contrast, the low-temperature process is affected by differences in gas diffusion resistance, and the radial chlorine gradient continues to accumulate, directly causing the deterioration of the optical uniformity of the finished product. This creates a technical contradiction that traditional processes cannot simultaneously achieve high optical uniformity and the absence of step defects. Based on the inherent density stratification characteristics of porous quartz powder, the bidirectional reaction mechanism of Si-Cl at high and low temperatures, and the gas diffusion law, this application adopts a multi-stage synergistic control core technology approach of high-temperature pre-shrinkage, reverse gradient pre-compensation, medium-high temperature gradient equalization calibration, and high-temperature gradient convergence cancellation, which solves the problems of refractive index abrupt change and non-uniformity in existing dechlorination processes.
[0030] Specifically, this application provides a method for preparing a low-hydroxyl synthetic quartz glass masterbatch, such as... Figure 1 As shown, it includes the following steps: S1. Powder pre-shrinking and homogenization stage: The porous quartz powder rod is heat-treated at 1250~1350℃ for several hours in an inert atmosphere to cause the porous quartz powder rod to shrink, reduce the overall density difference, and obtain the pre-shrinked porous quartz powder rod. S2, the low-temperature gradient pre-fabrication stage, involves introducing a He / Cl2 mixed gas at 700-900℃ to dehydroxylate the pre-shrinked porous quartz powder rod, simultaneously constructing a reverse chlorine gradient with a higher density at the outside and a lower density at the inside within the porous quartz powder rod. Normally, during the deposition of porous quartz powder, the lower temperature at the flame edge results in a porous quartz powder rod with a high density in the middle region and a low density at the edge region; this internal density distribution of the porous quartz powder rod with a lower density at the outside and a higher density at the inside is defined as a positive gradient. However, during the dehydroxylation process in step S2, a chlorine gradient with a higher density at the outside and a lower density at the inside is formed as chlorine gas diffuses, which is opposite to the gradient of the powder rod itself. Therefore, the chlorine gradient formed in step S2 is called a reverse chlorine gradient.
[0031] S3, the medium-temperature gradient equalization calibration stage, the temperature is raised to 850~950℃, and a He / O2 mixed gas is introduced for low-temperature dechlorination. At the same time, the reverse chlorine gradient formed in step S2 is homogenized to reduce the chlorine concentration gradient. The processing temperature in step S3 is 50~150℃ higher than that in step S2, but does not exceed 950℃. S4, the medium-high temperature gradient convergence and cancellation stage: He / O2 mixed gas is introduced at a temperature of 1000~1100℃ to carry out medium-high temperature dechlorination. During the high-temperature chemical reaction dechlorination process, the high density in the middle region and the low density in the edge region of the powder rod are utilized. The Cl contained in the middle region is difficult to diffuse out, while the Cl in the edge region is relatively easy to diffuse out and be removed, thus forming a chlorine gradient with a low outer and high inner density. This can cancel out the reverse chlorine gradient with a high outer and low inner density formed in step S2.
[0032] S5. Post-processing stage: After the high-temperature dechlorination in step S4 is completed, the temperature is raised by 50-200℃, and inert gas is introduced to purge the furnace body to remove free chlorine molecules inside the powder rod; then the temperature is lowered to room temperature to obtain powder rods that have completed dehydroxylation and dechlorination; the processing temperature in the post-processing stage of step S5 is 50-200℃ higher than that in step S4; the higher temperature increases the molecular diffusion rate, which is more conducive to the diffusion and discharge of chlorine inside the powder; inert gas is introduced to purge the furnace body, but oxygen, chlorine and other gases are not introduced, in order to remove local impurity enrichment areas in the powder rod, eliminate local chlorine enrichment in the powder rod, ensure uniform product quality, and completely remove free chlorine molecules inside the powder rod to prevent the powder rod from re-adsorbing in subsequent processes and causing a rebound in chlorine content.
[0033] S6. High-temperature transparent sintering stage: The powder rod obtained in step S5 is heated to 1450~1550℃, preferably 1480-1520℃, and isothermal transparent sintering is performed under an inert gas protective atmosphere to complete the densification and glassy transparent transformation of the powder rod, eliminating powder pores (i.e., powder rod pores) and micro-loose structure, and obtaining low-hydroxyl synthetic quartz glass matrix. Step S6 sintering at ultra-high temperature completes the densification and glassy transparent transformation of the powder blank, eliminates powder pores and micro-loose structure, solidifies a smooth radial chlorine distribution and continuous refractive index profile, and improves the density, light transmission uniformity and overall structural stability of the quartz glass matrix to obtain low-hydroxyl synthetic quartz glass matrix.
[0034] The method described in this application is applicable to porous silica bodies (also referred to as porous quartz powder rods) prepared from silicon chlorides via a hydrogen-oxygen flame hydrolysis vapor deposition process. These porous bodies possess suitable density and pore structure, enabling the production of low-hydroxyl (<1 ppm), high-purity, and low-defect quartz glass matrix materials during the chlorination-dehydroxylation, oxidative dechlorination, and high-temperature vitrification processes described in this application. The matrix can be prepared in-house or derived from commercially available similar products.
[0035] The method described in this application is applicable to porous quartz powder rods with a relatively large diameter range. In some embodiments, the porous quartz powder rod has a diameter of D200~D600mm and a bulk density of 0.25~0.5g / cm³, and there is a density gradient in the porous quartz powder rod, with a denser interior and a less dense exterior. This density gradient allows the powder rod blank to have different Cl removal rates inside and outside due to the density difference during the high-temperature treatment stage in step S4. The higher density at the center makes Cl removal difficult, while the lower density at the outside makes Cl removal easier, thus canceling out the reverse chlorine gradient formed after the equalization calibration in step S3.
[0036] The process object in step S1, the powder pre-shrinkage homogenization stage, of this application is quartz powder, a porous body of a certain density and size (i.e., porous quartz powder rods); the process temperature is 1250~1350℃, preferably 1260-1300℃; the heating rate is controlled at 4~7℃ / min to ensure stable heating and avoid thermal stress cracking and uneven local sintering of the green body. The process atmosphere is entirely protected by high-purity inert He gas at a flow rate of 20~30 slm; oxygen, chlorine, and any other reactive gases are strictly prohibited, ensuring only physical high-temperature sintering shrinkage occurs throughout the process. The process isothermal duration is 2~4 hours, preferably 3 hours, to ensure uniform radial and axial heating of the large-sized green body and achieve overall synchronous and gentle shrinkage. The core pretreatment objectives are: firstly, to effectively reduce the natural density difference of the powder blank from the center to the outer edge, weaken the layered structural defects remaining in the forming process, and regulate the micro-pore morphology of the blank, making the overall pore structure more uniform, thus providing a homogeneous substrate for subsequent gradient control and uniform dechlorination; secondly, to slightly reduce the overall diameter of the blank through moderate high-temperature physical shrinkage, shortening the mass transfer path of reactive gases such as chlorine and oxygen from the outer edge to the center of the blank in subsequent processes, reducing the difference in radial diffusion resistance, making the reaction and mass transfer in the inner and outer regions more synchronized, improving the control accuracy and uniformity of subsequent gradient preforming, calibration, and offsetting processes, and avoiding optical defect causes at the substrate level.
[0037] In some embodiments, in step S2, a He / Cl2 mixed gas with a flow rate of 20-30 slm is introduced to construct a reverse chlorine gradient with a higher outer layer and a lower inner layer in the porous quartz powder rod. The process duration t1 is calculated based on the Fick one-dimensional unidirectional gas penetration diffusion model according to the differences in powder rod diameter. ; ; In the formula: The duration of the gradient prefabrication process; The radial diffusion penetration depth of the powder rod; The effective diffusion coefficient of Cl2 in the low temperature range of 700~900℃; =20-40min; The gas-phase diffusion constant of Cl2; The porosity of the powder; This refers to the tortuosity of the duct. The processing time at this stage is positively correlated with the square of the radial dimension of the billet, and is adapted according to the differences in billet diameter. In a preferred embodiment, the processing temperature in step S2 is 750~850℃.
[0038] Step S2 is the reverse gradient pre-formation and dehydroxylation treatment stage.
[0039] Process temperature: 700~900℃, preferably 750-850℃, which is a dedicated safe temperature zone for low temperature gradient prefabrication, avoiding high temperature deformation and shrinkage defects of powder, and laying the foundation for subsequent gradient temperature control design.
[0040] Process atmosphere: High-purity He is used as the carrier gas, with a flow rate of 15~35 slm, preferably 20~30 slm; anhydrous Cl2 is introduced as the chlorinating agent, with a flow rate of 0.3~2 slm, preferably 0.5~1.5 slm; no oxygen is introduced throughout the process.
[0041] Processing time: Based on the quantitative derivation of the unidirectional diffusion formula, a diameter-differentiated time control mechanism is adopted to adapt to full-size blanks; by matching the size with a dedicated time, the uniform gradient forming of blanks of various specifications is ensured.
[0042] Core function: To address the diffusion differences of ultra-large powder rods with different diameters, differential timing is controlled based on diameter linkage, with a delay of 20-40 minutes to achieve slight over-chlorination at the edges of powder rods of various sizes. Combined with the density characteristics of the powder rods being denser inside and sparser outside, a stable and uniform primary reverse chlorination gradient with higher outer and lower inner chlorination can be formed in powder rods of the entire size range of D200~600mm. At the same time, the hydroxyl content of the entire cross section is guaranteed to be <0.5ppm. There are no refractive index step defects in this stage, and it does not affect the overall mass production efficiency.
[0043] In some embodiments, step S3 introduces a He / O2 mixed gas with a total flow rate of 10~30 slm, and the process duration t2 is calculated based on the bidirectional diffusion equilibrium mechanism according to the differences in powder rod diameter. ; In the formula: This refers to the gradient calibration equalization process duration; The diffusion coefficient of He / O2 mixed gas within the intermediate temperature calibration range of 850~950℃ ( D 2. Acquisition Method: A microporous ceramic sampling probe is pre-embedded in the center of a porous body of the same size and density prepared using the same process. The bodies are then placed together in a gas atmosphere with the same process parameters. Real-time monitoring of the internal helium and oxygen concentrations within the product is conducted. The average value after steady-state convergence, based on multiple sets of time-series concentration change data, is taken as the effective diffusion coefficient of the He / O2 mixed gas. This temperature range exhibits stable operating conditions and minimal diffusion characteristic fluctuations, with an overall diffusion rate higher than that of the 700-900℃ low-temperature chlorine diffusion condition in step S2. Other powder structure parameters ( The radial diffusion penetration depth of the powder rod; The porosity of the powder; The tortuosity of the duct is completely consistent with step S2 to ensure system consistency. The duration of this stage increases regularly with the radial dimension of the billet, adapting to the requirements of full-size billet balance calibration.
[0044] Step S3 is the gradient adjustment stage (low-temperature pre-dechlorination calibration).
[0045] Process temperature: 850~950℃, preferably 875-925℃; compared with the pre-prepared temperature zone in step S2, the overall temperature is increased by 50~150℃, forming a gradient progressive temperature control logic, and the maximum temperature is strictly limited to within 950℃, which not only improves the dynamic of chlorine diffusion equilibrium, but also avoids structural defects caused by premature densification of powder.
[0046] Process atmosphere: High-purity He flow rate 5~20 slm, preferably 10-15 slm; High-purity O2 flow rate 2~6 slm.
[0047] Process time: Based on the quantitative derivation of the two-way balance formula, it matches the diffusion balance requirements of billets with different diameters; the diffusion path of large-size billets is longer, and the corresponding calibration time is longer, so as to realize the gradient synchronous balance calibration of full-size billets.
[0048] Core Function: This process employs a dual control mechanism of constant temperature and oxygen partial pressure + diameter-differentiated time, solving the problem of poor size adaptability in traditional fixed-time processes. 875-925℃ is a dedicated critical temperature range for gradient calibration, which can uniformly weaken the dechlorination rate differences caused by radial density stratification of powder. Combined with a fixed oxygen partial pressure, the dedicated calibration time ensures sufficient diffusion balance across all sizes of the green body, allowing the chlorine gradient in the green body to decrease stably and linearly, providing a uniform and stable precondition for the subsequent full offsetting of the high-temperature gradient.
[0049] In some embodiments, step S4 introduces a He / O2 mixed gas at a flow rate of 20-30 slm, and heats the gas to 1000-1100°C at a heating rate of 1-8°C / min to carry out a high-temperature chemical reaction. The process duration t3 is calculated based on a high-temperature solid solution reaction kinetic model. ; In the formula: This refers to the duration of the high-temperature gradient offset reaction process; This represents the average chlorine content in the powder bar (the powder bar is the one before the end of step S3 and the start of step S4). For gradient cancellation balancing efficiency; The reaction rate constant is at 1050℃; This is the partial pressure of oxygen. This represents the effective reaction surface area of the powder. The duration of this stage is determined by high-temperature chemical kinetic parameters and is independent of the billet size, making it suitable for billets of all sizes from D200 to 600 mm. The average chlorine content in the powder rod is also included. The method for obtaining samples is as follows: Test samples of the same specifications (same size, density, and weight) are placed in the same processing equipment, and step S3 is completed using the same gas atmosphere with the same process parameters. After cooling, multiple sets of samples are taken at equal intervals from the center to the edge. The chlorine concentration of each product is tested using ICP-MS, and the average value is calculated. Gradient cancellation equilibrium efficiency. The calibration experiment can be conducted offline under constant temperature and oxygen conditions. Specifically, under a fixed temperature (e.g., 1050℃) and a fixed ratio and flow rate of high-purity He / O2 mixed gas, the known values obtained from the aforementioned process can be analyzed. High-temperature gradient offsetting experiments were conducted on samples at different times. Chlorine elimination rate-time curves were fitted based on the changes in chlorine content before and after the reaction. The relative equilibrium efficiency corresponding to reaching the set chlorine residue threshold was taken as η, and an empirical value range was determined after multiple batches of calibration. The reaction rate constant at 1050℃ was also considered. The k value can be obtained by fitting kinetic experimental data at multiple temperature points (i.e., selecting several temperature points within the range of 1000~1100℃, measuring the instantaneous reaction rate under the same oxygen partial pressure and atmosphere, plotting ln(k) against 1 / T, and thus calculating the k value corresponding to 1050℃; alternatively, a verified k value from literature of the same system can be used as a process constant); oxygen partial pressure Data is obtained in real-time online testing using an external oxygen pressure sensor connected to the powder rod; effective reaction surface area of the powder. It can be obtained by testing with a specific surface area and porosity analyzer (BET analyzer).
[0050] In some embodiments, step S4 uses a heating rate of 1~2℃ / min to raise the temperature to the critical range of solid solution reaction of 950~1000℃, while in other heating ranges a heating rate of 3~7℃ / min is used.
[0051] Step S4 is the dynamic convergence and cancellation stage of the medium and high temperature gradient (core dechlorination stage).
[0052] Process temperature: 1000~1100℃, preferably 1020-1080℃.
[0053] Process atmosphere: High-purity He flow rate 15~35 slm, preferably 20-30 slm; High-purity O2 flow rate 1.0~6.0 slm, preferably 2-5 slm.
[0054] Process time: Based on the quantitative derivation of the high-temperature reaction kinetic formula, it ensures that the high-temperature solid solution reaction of all specifications of billets is thorough and the gradient is fully offset.
[0055] Heating mechanism: The entire process is controlled by graded and differentiated heating. The basic heating rate is 3~7℃ / min, preferably 5℃ / min. In the critical range of solid solution reaction of 950~1000℃, an ultra-slow heating rate of 1~2℃ / min is adopted, preferably 1.5℃ / min, to gently activate the solid solution reaction and avoid instantaneous changes in the solid-solid ratio, thus inhibiting the formation of steps from the source. After heating to the high temperature range, the temperature fluctuates slightly to stabilize it, adapting to the dynamic changes of the radial gradient of the powder rod.
[0056] Core function: Under the standard high-temperature mass production system, it achieves dynamic and full cancellation of the pre-prepared reverse gradient and the inherent high-internal and low-external solid solution gradient at high temperature; it weakens the chlorine distribution deviation caused by density inhomogeneity, further reduces the radial abrupt change amplitude of solid solution ratio, eliminates the discontinuous abrupt change step of refractive index, and at the same time relies on the high-temperature solid solution effect to ensure excellent optical uniformity performance, thus achieving both mass production efficiency and high-end optical performance.
[0057] In some embodiments, in step S5, pure He gas with a flow rate of 20-30 slm is introduced to purge for 150-250 min; then the temperature is reduced to room temperature at a rate of 1-5 °C / min.
[0058] In some embodiments, step S6 involves introducing 20-30 slm of pure He and sintering at a constant temperature for 120-180 minutes.
[0059] The process involves a segmented approach: after high-temperature dechlorination, the material undergoes inert gas purging and isothermal post-treatment, followed by a gradient heating to ultra-high temperatures for transparent sintering. This step-by-step control method of "locking the gradient first, then densifying" avoids issues such as compositional shifts, stress defects, and gradient failures. It achieves impurity removal, gradient locking, and compaction and transparency of the green body in stages, significantly improving the density and optical uniformity of the finished product. Utilizing ultra-high temperatures of 1450~1550℃, the powder green body is densified and the glassy transparency is transformed, eliminating powder pores and microscopic loose structures, solidifying a smooth radial chlorine distribution and a continuous refractive index profile. This prevents secondary compositional shifts and minor defects caused by low-temperature cooling and reheating, significantly improving the density, light transmission uniformity, and overall structural stability of the quartz glass matrix.
[0060] Step S1, powder pre-shrinking and homogenization, is the core foundational step of the entire gradient control process, with a process temperature range of 1250~1350℃. The original porous quartz preform prepared by vapor deposition naturally possesses structural defects such as uneven radial density from the center to the outside and disordered pores. Directly implementing dechlorination gradient control would result in significant diffusion resistance differences, leading to an imbalance in mass transfer and reaction rates, forming a disordered chlorine concentration gradient. Through a physical pre-shrinking process in a pure inert helium atmosphere at this temperature range, the radial density difference of the preform can be effectively reduced, the microporous structure can be regularized and connected, and the problems of local pore blockage and uneven density can be eliminated. Simultaneously, the moderate shrinkage of the preform shortens the radial mass transfer path of reactive gases such as oxygen and chlorine from the surface to the core, weakening the diffusion resistance differences and allowing subsequent gas permeation stages to proceed continuously rather than in a gradient manner, providing a homogeneous and stable preform substrate for gradient pre-forming and offsetting.
[0061] Step S2, the low-temperature gradient pre-fabrication stage, is a crucial preliminary step in constructing a controllable reverse chlorine gradient, with a process temperature range of 700~900℃. This stage utilizes this low-temperature range and a process atmosphere of helium-containing Cl2 mixed gas. Leveraging the homogeneous porous channels formed by pre-shrinkage in step S1, the mixed gas components diffuse unidirectionally, uniformly, and stably from the outer layer of the green body to the core layer. Unlike the traditional disordered chlorination method using a single chlorine gas, the homogeneous green body has no local diffusion barriers, resulting in a more consistent permeation rate of the mixed gas across the green body cross-section. This allows for the pre-fabrication of a well-defined, uniformly distributed "high on the outside, low on the inside" reverse chlorine concentration gradient under controllable diffusion conditions. This gradient is a pre-set, controllable gradient, not a naturally occurring defect gradient. It can match the inherent gradient of high on the inside and low on the outside generated by subsequent high-temperature solid solution treatment, providing a precise initial base for bidirectional gradient offsetting. This fundamentally solves the problems of disordered chlorine gradients, uncontrollable amplitudes, and the inability to eliminate gradient values in traditional processes.
[0062] Step S3, the temperature equalization calibration stage, is a process to further regulate chlorine distribution and reduce radial concentration deviation, with a process temperature range of 850~950℃. In this stage, based on the low-temperature gradient pre-forming in step S2, the temperature is moderately increased, continuing to use an oxygen and helium mixed atmosphere system without introducing chlorine. However, chlorine remains inside the billet at this point. Relying on the uniformly permeable pore structure after pre-shrinking, oxygen and residual chlorine diffuse synchronously and uniformly across the entire cross-section of the billet. Thanks to the improved powder density consistency after pre-shrinking, there is no significant gradient difference in gas diffusion resistance between the inner and outer regions, allowing the oxidative dechlorination reaction to occur simultaneously in both the surface and core layers of the billet. By fully participating in the oxidative dechlorination reaction, the amplitude of the reverse chlorine gradient pre-formed in step S2 is weakened, the chlorine concentration distribution curve is smoothed, and the chlorine concentration difference from the center to the outer side of the billet is significantly reduced. This controls the originally distinct chlorine distribution gradient to a uniform and stable transition state, laying the optimal pre-distribution conditions for subsequent high-temperature complete offsetting.
[0063] Step S4, the high-temperature gradient convergence and cancellation stage, is the core and critical process for completely eliminating the chlorine gradient and eradicating optical defects. The process temperature range is 1000~1100℃. This stage relies on the high-temperature chemical reaction kinetics mechanism to activate the silicon-chlorine solid solution reaction and deep oxidation dechlorination reaction within the quartz powder. Due to slight inherent density differences, the green body spontaneously generates an inherent chlorine gradient with a higher internal gradient and a lower external gradient. This gradient, combined with the previously pre-calibrated reverse chlorine gradient (higher external gradient and lower internal gradient), forms a bidirectional offsetting system. Through ultra-slow temperature control within the 1000~1100℃ solid solution critical range, the global solid solution reaction is gently activated, avoiding new concentration steps caused by sudden changes in local reaction rates. Within the 1000~1100℃ high-temperature isothermal range, the bidirectional gradient continuously and dynamically converges and fully cancels out the gradient, completely smoothing out the radial chlorine concentration distribution differences within the green body. This achieves a highly uniform chlorine concentration across the entire green body, eliminating refractive index fluctuations and potential optical distortions at their source.
[0064] Step S5, the post-treatment stage, is a crucial transitional purification process that thoroughly removes free chlorine, prevents chlorine content rebound, and connects to the high-temperature sintering process. This stage has no fixed constant temperature range; the process temperature is increased by 50-200°C from the temperature at which the high-temperature gradient offset in step S4 ends. The overall temperature is lower than the subsequent high-temperature sintering temperature to avoid premature sealing of the pores in the green body. After the gradient offset in step S4, the chlorine concentration inside the green body is generally uniform, but a large amount of free chlorine and trace amounts of unremoved chlorine components remain in the pipe walls and pores. These can easily re-permeate the green body during the subsequent high-temperature sintering process, causing a chlorine content rebound and the re-formation of the concentration gradient. This stage uses pure helium purging and replacement throughout. Utilizing the stable, inert, and non-reactive properties of helium, it continuously flushes the pipes and the micropores of the green body, efficiently removing free chlorine, residual gaseous chlorides, and other impurities from the system. Meanwhile, moderate heating can further activate the pore channels, improve the diffusion and release efficiency of free chlorine, clear the residual chlorine components in the green body and tubes, reduce the risk of chlorine rebound, stabilize the uniform chlorine distribution structure throughout the green body, and provide pure green body conditions without residual chlorine and impurity contamination for the subsequent high-temperature transparent sintering process.
[0065] Step S6, the high-temperature transparent sintering stage, is the crucial final step in achieving optical property solidification and compaction of the green body. The process temperature range is 1450~1550℃, preferably 1500℃. After the first five stages of gradient control and homogenization treatment, the green body has a uniform microstructure and no gradient deviation in chlorine distribution. The high-temperature sintering stage, through densification treatment in a high-temperature inert atmosphere, allows the porous quartz powder to be completely melted and densified, completing the glass phase transition. During the high-temperature melting and reconstruction process, the residual trace stress and micropores inside the green body are completely eliminated, and the originally uniform chlorine distribution and refractive index structure are permanently solidified, preventing secondary gradient differentiation due to the high-temperature phase transition. The final product is a high-purity quartz glass with no chlorine concentration steps, no refractive index distortion, and excellent global optical uniformity.
[0066] This application proposes a composite dechlorination process for synthetic quartz glass substrate, which for the first time simultaneously breaks through the dual limits of optical uniformity and step, solves the industry problem of discontinuous and abrupt fluctuations in refractive index profile during high-temperature dechlorination, and is compatible with the integrity of the preform structure and optical performance, thus resolving the technical contradictions of traditional processes.
[0067] The process described in this application is compatible with a wide range of specifications, including D200mm, D350mm, and D600mm, and can be adapted to billets of different diameters by fine-tuning the time.
[0068] The embodiments of this application are implemented based on the technical solution of this application, and detailed implementation methods and processes are given. However, the protection scope of this application is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally based on conventional conditions.
[0069] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application.
[0070] Example 1 Test subject: Mass-produced large-size porous quartz powder rods with a diameter of 600mm and a bulk density of 0.35g / cm³ were selected. The green body has a natural radial and axial density layered structure, which is a conventional mass-produced green body in the industry. The specific steps for preparing the low-hydroxyl synthetic quartz glass masterbatch in this embodiment are as follows: 1. Powder pre-shrinking and homogenization stage: The porous quartz powder rod is heat-treated at 1280℃ for 3 hours in a high-purity inert He atmosphere to shrink the porous quartz powder rod, reduce the overall density difference, and obtain the pre-shrinked porous quartz powder rod.
[0071] 2. Low-Temperature Gradient Pre-fabrication Stage: The process temperature is 800℃, with 25 slm of high-purity He + 1.0 slm of anhydrous Cl2 introduced, creating a completely oxygen-free environment. The duration of this stage is calculated quantitatively based on the unidirectional penetration diffusion formula, with the following parameter fixed: the effective low-temperature diffusion coefficient. =3.0× m² / s =7.5× duct tortuosity Powder porosity The effective radial diffusion depth of the D600mm billet is x=0.6m. Substitute into the formula Calculation: The process involves precise formula calculations to complete the deep dehydroxylation and reverse gradient prefabrication of the billet, forming a reverse chlorine gradient with a high outer layer and a low inner layer, resulting in a hydroxyl content of <0.5ppm across the entire cross-section of the billet.
[0072] Since the structure of the produced powder cannot be damaged, the calibration sample needs to be sampled and analyzed at each process using a new blank. That is, a new powder is used alone, and samples are taken and prepared at each step. The chlorine content is tested using ICP-MS tandem triple quadruple mass spectrometry. Samples are taken along the diameter direction on the central cross-section of the product of a certain thickness to obtain the chlorine content distribution.
[0073] 3. Medium-Temperature Gradient Equilibrium Calibration Stage: The process temperature is 900℃, a 100℃ increase from the previous stage, and 12 slm of high-purity He + 4 slm of high-purity O2 are introduced. This stage quantifies the calculation time based on the bidirectional diffusion equilibrium formula. The core calculation formula is... Each powder structure parameter adopts a constant standard value for mass production, specifically: radial diffusion depth. Effective diffusion coefficient of mixed gas in the intermediate temperature range , channel tortuosity Powder porosity Complete calculation by substituting parameters: The calibration time for a D600mm billet was found to be 300 minutes. By relying on the dual control mechanism of constant oxygen partial pressure and size-differentiated time, the radial dechlorination rate of the powder was balanced, the diffusion difference caused by the uneven density of the billet was offset, and the reverse gradient formed in step S2 was further reduced to a lower level. The refractive index profile of the billet was smooth and defect-free throughout the process, providing suitable matching conditions for the subsequent high-temperature gradient to be fully offset.
[0074] 4. Dynamic Convergence and Cancellation Stage of Medium- and High-Temperature Gradients: A staged heating mode is adopted, with a heating rate of 5℃ / min in the normal range and a slow heating rate of 1.5℃ / min in the critical range of 950~1000℃, finally stabilizing at 1050℃, and then introducing 25slm of high-purity He + 3slm of high-purity O2. The duration of this stage is quantitatively derived based on the high-temperature chemical reaction kinetic formula. The core calculation formula is as follows: All parameters are constant parameters used in standard mass production at 1050℃. Specific values are: average chlorine content of the billet. Gradient cancellation balance efficiency Rate constant of solid solution reaction at 1050℃ oxygen partial pressure Effective reaction surface area of powder The parameters throughout the process are unrelated to the radial dimension of the billet, and are suitable for billets with a diameter of D200~600mm. Substitute these parameters into the calculation: The final result showed that the uniform constant temperature reaction time for the D600mm billet was 134 minutes.
[0075] 5. Post-treatment stage: 25 slm of pure He was continuously purged at a high temperature of 1150℃ for 200 min. Then, the temperature was lowered to room temperature at a rate of 3℃ / min.
[0076] 6. High-temperature transparent sintering stage: After room temperature reset, the temperature is raised to 1500℃ at a steady rate of 4℃ / min, and a 25slm high-purity He protective atmosphere is maintained throughout the process. The sintering is carried out at a constant temperature for 150min to complete the densification of the green body, the complete transparent transformation of the glass body, and the solidification of the optimal optical structure.
[0077] 7. Finished Product Output: After sintering, the product is naturally kept warm and cooled to obtain a high-end quartz glass masterbatch with high density, no steps, and high gloss uniformity.
[0078] Finished product test results: The solidified thick glass rod has a diameter of approximately 300mm (D300mm). The finished product light intensity is 1.62ppm, the step depth is <0.5ppm, the number of steps is zero, the refractive index profile shows no discontinuous or abrupt fluctuations, and is continuously smooth throughout without local optical distortion; the total hydroxyl content is <0.5ppm, the impurity content is low, the preform structure is dense and complete without porosity or deformation, and the light transmission uniformity is excellent, fully meeting the requirements of high-end optical applications. Figure 2 and Figure 3 As shown.
[0079] Example 2 The rest is the same as in Example 1, except that a D300mm porous quartz powder rod is used, and the process time of the low-temperature gradient prefabrication and medium-temperature gradient calibration stages is adaptively adjusted according to the diffusion kinetics formula. The specific steps are as follows: S1: Same as Example 1 S2: Low-Temperature Gradient Pre-Preparation Stage: Process temperature 800℃, atmosphere 25slm high-purity He + 1.0slm anhydrous Cl2, completely oxygen-free. The duration and effective low-temperature diffusion coefficient are calculated using the unidirectional penetration diffusion formula. =3×10 -5 m² / s, effective radial diffusion depth of D300mm billet x=0.3m, substituting into the formula Calculation: The process involves precise formula calculations to determine the time required for deep dehydroxylation and reverse gradient prefabrication of the green body, resulting in a reverse chlorine gradient with a high outer layer and a low inner layer. The hydroxyl content across the entire cross-section of the green body is less than 0.5 ppm.
[0080] S3 Temperature Gradient Equilibrium Calibration Stage: This stage quantifies the calculation time based on the bidirectional diffusion equilibrium formula. The calculation formula is as follows: Each powder structure parameter adopts a constant standard value for mass production, specifically: radial diffusion depth. Effective diffusion coefficient of mixed gas in the intermediate temperature range , channel tortuosity Powder porosity Complete calculation by substituting parameters: The calibration time for a D300mm billet was found to be 75 minutes.
[0081] The other steps are the same as in Example 1.
[0082] Comparative Example 1 The rest is the same as in Embodiment 1, except that step S1 is omitted (i.e., we start directly from step S2).
[0083] Comparative Example 2 The rest is the same as in Example 1, except that after steps S1 and S2 are completed, the temperature is directly increased from 800°C in step S2 to 1050°C in step S4 at a rate of 4°C / min, and step S4 is performed. During this process, 25 slm of high-purity He + 1.0 slm of anhydrous Cl2 are introduced, creating an oxygen-free environment throughout. The Cl2 is turned off when step S4 begins.
[0084] Comparative Example 3 Test subject: exactly the same as in Example 1, using porous quartz powder rods with a diameter of 600mm and a bulk density of 0.35g / cm³.
[0085] This comparative example adopts the industry-standard high-temperature variable-temperature dechlorination process, which not only eliminates the core processes of reverse gradient pre-formation and gradient calibration in this application, but also uses a fixed process duration and fixed temperature parameters throughout the entire process, without any differential control mechanism for the powder rod diameter. The specific process steps and fixed parameters are as follows: 1. Conventional low-temperature dehydroxylation stage: The process temperature is 800℃, 25slm high-purity He + 1.0slm anhydrous Cl2 are introduced, and the entire process is carried out in an oxygen-free environment. The temperature is kept constant for 320 minutes to complete the basic dehydroxylation.
[0086] 2. Direct heating stage: There is no process for adjusting the chlorine concentration gradient inside and outside the product. The temperature is directly increased at a constant rate of 5℃ / min. No slow temperature control is performed in the solution critical range of 950~1000℃. The temperature is increased at a constant rate to 1050℃ throughout the process.
[0087] 3. High-temperature dechlorination and post-treatment stage: The temperature is kept constant at 1050℃, and 25slm high-purity He + 3slm high-purity O2 is introduced and kept at the constant temperature for 450min to complete the high-temperature dechlorination; then 25slm pure He is introduced to purge for 200min, and the temperature is reduced to room temperature at 3℃ / min. There is no gradient calibration or high-temperature transparent sintering densification process.
[0088] 4. Firing and Transparency Stage: After room temperature reset, the temperature is increased to 1500℃ at a steady rate of 4℃ / min, and a 25slm high-purity He protective atmosphere is maintained throughout the process. The temperature is kept constant for 150min until transparent sintering is completed.
[0089] Finished product test results: After firing, the glass rod size is 300mm, the finished product light is 9.17ppm, the step depth is about 3ppm, there are obvious refractive index fluctuation steps, the refractive index profile is discontinuous and abruptly fluctuates, and there is local optical distortion; the total hydroxyl content is <0.7ppm; the reaction process is seriously mismatched with the size, the gradient is completely out of control, a large area of chlorine concentration drops sharply in the cross section, and there are a lot of discontinuous and abrupt step fluctuations in the refractive index profile.
[0090] Table 1. Performance characterization results of the quartz glass matrix materials prepared in the examples and comparative examples.
[0091] As can be seen from Table 1, Examples 1 and 2 adopted an integrated composite process including a powder pre-shrinking homogenization stage, a low-temperature gradient pre-fabrication stage, a medium-temperature gradient equalization calibration stage, a medium-high temperature gradient convergence and cancellation stage, a post-treatment stage, and a final high-temperature transparent sintering stage. The difference in Cl content between the center and the edge of the prepared synthetic quartz glass matrix was only 3-4 ppm, while that of Comparative Examples 1 to 3 was as high as 20 ppm or more. Furthermore, the total hydroxyl content of the synthetic quartz glass matrix of the Examples was <0.5 ppm, and the optical non-uniformity value of 90% of the entire product area was less than 2 ppm, all of which were significantly better than those of the Comparative Examples.
[0092] Figure 2 After grinding and polishing, the product produced in Example 1 of this application was tested for internal optical inhomogeneity using the industry-recognized Zygo equipment. The interferogram showed no obvious rings across the entire cross section and the uniform color distribution indicated that the radial chlorine concentration inside the product was uniform, with no obvious optical distortion and uniform radial refractive index. The test value was 1.62 ppm for optical inhomogeneity at a D300mm aperture.
[0093] Figure 3 The image shows the one-dimensional transmission wavefront distortion profile curve measured by an interferometer after the product of Example 1 of this application passes through the test material via laser transmission. The curve is scanned from one side to the other along the diameter direction, testing the two directions of the crosshair. The horizontal axis is the laser transmission scanning distance (mm), and the vertical axis is the equivalent wavefront distortion amplitude (nm). The curve shows that the detection path changes uniformly in the diameter direction without obvious fluctuations, which corresponds to a continuous and uniform refractive index profile.
[0094] Figure 4 After grinding and polishing, the product produced for Comparative Example 2 of this application was tested for internal optical inhomogeneity using the industry-recognized Zygo equipment. The interferogram showed multiple layers of regular concentric ring-shaped bright and dark fringes on the cross section, indicating that the radial chlorine concentration inside the product continuously accumulated at a gradient, the refractive index profile fluctuated violently, resulting in irreversible optical distortion, and the radial refractive index changed abruptly layer by layer, forming multiple optical inhomogeneous steps.
[0095] Figure 5 The image shows the one-dimensional transmission wavefront distortion profile curve measured by an interferometer after the laser passes through the material under test, as shown in Comparative Example 2 of this application. The test crosshairs are in two directions. The horizontal axis represents the laser transmission scanning distance (mm), and the vertical axis represents the equivalent wavefront distortion amplitude (nm). The curve shows that there are multiple sets of periodic wavefront distortion fluctuations in the detection path, which correspond to discontinuous and abrupt fluctuations in the refractive index profile and local optical distortion.
[0096] Comparative Example 3 synthesizes quartz glass matrix using traditional processes and a fixed parameter system. It lacks differentiated control logic for ultra-large span sizes from D200 to 600mm, and can only be adapted to mass production of single-specification blanks, resulting in extremely poor adaptability. At the same time, the process cannot actively control the chlorine gradient distribution inside the blank. Under low-temperature conditions, the chlorine gradient is prone to continuous accumulation, leading to poor light uniformity of the finished product. Under high-temperature conditions, the natural density stratification of the powder will cause irreversible chlorine concentration mutations, which solidify into permanent refractive index steps and optical distortions. It is impossible to achieve both high light uniformity and defect-free forming effect.
[0097] The proposed method for preparing low-hydroxyl synthetic quartz glass masterbatch includes a powder pre-shrinkage homogenization stage, a low-temperature gradient pre-fabrication stage, a medium-temperature gradient equalization calibration stage, a medium-high temperature gradient convergence and cancellation stage, a post-processing stage, and a final high-temperature transparent sintering stage. It can fully cover the production of ultra-large span blanks from D200 to 600 mm, precisely adapting to the gas diffusion differences of blanks with different diameters, and eliminating refractive index abrupt defects through a bidirectional gradient offsetting principle. Experimental results show that this method can stably achieve a light uniformity of 1.62 ppm, a full-diameter hydroxyl content of <0.5 ppm, a step depth of <0.5 ppm, and zero step count in finished glass rod masterbatch slices with a D300 mm diameter, with a continuous and smooth refractive index profile and no optical distortion. Simultaneously, it ensures a dense and complete blank structure, completely solving the core industry contradiction of traditional processes—difficulty in adapting to multiple sizes and the inability to simultaneously achieve high light uniformity and no step distortion. It combines excellent mass production versatility with high-end optical performance, demonstrating significant technological advancement and practical value.
[0098] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for preparing a low-hydroxyl synthetic quartz glass matrix, characterized in that, Includes the following steps: S1. The porous quartz powder rod is heat-treated in an inert atmosphere at 1250~1350℃ for several hours to cause the porous quartz powder rod to shrink, reduce the overall density difference, and obtain the pre-shrinked porous quartz powder rod. S2. At a temperature of 700~900℃, a He / Cl2 mixed gas is introduced to perform dehydroxylation treatment on the pre-shrinked porous quartz powder rod, while simultaneously constructing a reverse chlorine gradient with a high outer and low inner temperature within the porous quartz powder rod. S3. Heat to 850~950℃, introduce He / O2 mixed gas for low-temperature dechlorination, and at the same time homogenize the reverse chlorine gradient formed in step S2 to reduce the chlorine concentration gradient; the processing temperature of step S3 is 50~150℃ higher than that of step S2 but does not exceed 950℃. S4. At a temperature of 1000~1100℃, a He / O2 mixed gas is introduced to carry out medium-high temperature dechlorination. During the high-temperature chemical reaction dechlorination process, taking advantage of the high density in the middle region and the low density in the edge region of the powder rod, the Cl contained in the middle region is difficult to diffuse out, while the Cl in the edge region is relatively easy to remove, forming a chlorine gradient with a low outer and high inner density. This cancels out the reverse chlorine gradient with a high outer and low inner density formed in step S2. In step S4, the temperature is increased at an ultra-slow rate of 1~2℃ / min in the critical range of solid solution reaction of 950~1000℃, and the temperature is increased at a rate of 3~7℃ / min in other temperature ranges. S5. After the high-temperature dechlorination in step S4 is completed, the temperature is raised to 50-200℃, and inert gas is introduced to purge the furnace body to remove free chlorine molecules in the powder rod; then the temperature is lowered to room temperature to obtain the powder rod that has completed dehydroxylation and dechlorination. S6. The powder rod obtained in step S5 is heated to 1450~1550℃ and subjected to constant temperature transparent sintering under an inert gas protective atmosphere to complete the densification and glassy transparent transformation of the powder rod, eliminate powder pores and micro-loose structure, and obtain low hydroxyl synthetic quartz glass matrix.
2. The preparation method according to claim 1, characterized in that, The porous quartz powder rod has a diameter of D200~D600mm and a bulk density of 0.25~0.5g / cm³.
3. The preparation method according to claim 1, characterized in that, In step S1, the heating rate is controlled at 4~7℃ / min, and the heating time is 2-4h.
4. The preparation method according to claim 1, characterized in that, In step S2, a He / Cl2 mixed gas with a flow rate of 20~30 slm is introduced to construct a reverse chlorine gradient with a higher outer layer and a lower inner layer in the porous quartz powder rod. The process duration t1 is calculated based on the Fick one-dimensional unidirectional gas penetration diffusion model, taking into account the differences in powder rod diameter. ; ; In the formula: The duration of the gradient prefabrication process; The radial diffusion penetration depth of the powder rod; The effective diffusion coefficient of Cl2 in the low temperature range of 700~900℃; =20-40min; The gas-phase diffusion constant of Cl2; The porosity of the powder; The degree of tortuosity of the passageway.
5. The preparation method according to claim 4, characterized in that, Step S3 introduces a He / O2 mixed gas with a total flow rate of 10~30 slm. The process duration t2 is calculated based on the bidirectional diffusion equilibrium mechanism and the difference in powder rod diameter. ; In the formula: The diffusion coefficient of He / O2 mixed gas within the medium-temperature calibration range of 850~950℃.
6. The preparation method according to claim 1, characterized in that, The process time t3 for step S4 is calculated based on the high-temperature solid solution reaction kinetic model: ; In the formula: This represents the average chlorine content in the powder bar; For gradient cancellation balancing efficiency; The reaction rate constant is at 1050℃; This is the partial pressure of oxygen. This represents the effective reaction surface area of the powder.
7. The preparation method according to claim 1, characterized in that, In step S5, pure He gas with a flow rate of 20-30 slm is introduced to purge for 150-250 min; then the temperature is reduced to room temperature at a rate of 1-5 °C / min.
8. The preparation method according to claim 1, characterized in that, In step S6, 20-30 slm of pure He gas is introduced and sintered at a constant temperature for 120-180 min.
Citation Information
Patent Citations
Method for producing quartz casing tube for optical fiber prefabricated stick
CN101314515A
Preparation method of ultralow-loss optical fiber preform and ultralow-loss optical fiber preform
CN118343993A